A fossil gnetalean leaf with evidence of insect mining from the Upper Triassic of Mendoza, Argentina - Cariglino, Barbara (2021)
Leaf mines are endophytic traces produced by larvae from the Diptera, Coleoptera, Hymenoptera or Lepidoptera when feeding on the tissue in between the epidermises of the leaf. Although there are a few mentions from the Late Paleozoic, the earliest unequivocal leaf mine is found in Lower Triassic deposits from Russia. Still, the pre-Cretaceous record of leaf mining remains meager and rare. Despite being more infrequently preserved in comparison to other types of plant arthropodinteractions (both endophytic and exophytic), the identification of Triassic leaf mines in Gondwanan deposits has considerably increased in the last years, and has been documented predominantly on voltzialean Heidiphyllum leaves, but also on pteridosperm, ginkgoalean and cycadalean leaves from Brazil, South Africa and Australia. Here, we present a mine trace on a fossil leaf from the Carnian (~232 My) Quebrada del Durazno locality, uppermost section of the Potrerillos Formation, in Mendoza province (Argentina). The specimen IANIGLA-PB 97 a-b consists of the impression of a gnetalean Yabeiella brackebuschiana leaf bearing a linear mine trace. The leaf mine is positioned at the middle part, on one side of the leaf lamina. It is 15 mm long (measured as a straight line from start to end) and is characterized as a mostly linear trace with some wide turns. The trace keeps almost the same width all along, and its path crosses the secondary veins but never theprimary vein of the leaf. Small, rounded 0.2 mm in diameter pellets (frass) are present throughout the mine. The Quebrada del Durazno locality comprises an abundant Dicroidium flora in association to a rich paleoentomofauna, among which hemipterans, mecopterans, orthopterans, odonatans, grylloblattids, dipterans and coleopterans can be found. Out of the possible producers of the leaf mine herein presented, beetles seem the most likely candidates, although an unquestionable attribution is at present unattainable. Finally, this is the first leaf mine recorded for the Cuyana Basin, adding to another single Triassic Argentinean mention of a mine trace from the Norian Laguna Colorada Formation in Santa Cruz province. This finding expands the current wealth of information on plant-arthropod interactions gathered from several field work seasons at the Potrerillos Formation and increases the number of identified insect damages currently under examination by this research group.